2021
DOI: 10.3390/biomedicines9070782
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Lipoprotein Lipase Regulation in Atherosclerosis

Abstract: Lipoprotein lipase (LPL) plays a major role in the lipid homeostasis mainly by mediating the intravascular lipolysis of triglyceride rich lipoproteins. Impaired LPL activity leads to the accumulation of chylomicrons and very low-density lipoproteins (VLDL) in plasma, resulting in hypertriglyceridemia. While low-density lipoprotein cholesterol (LDL-C) is recognized as a primary risk factor for atherosclerosis, hypertriglyceridemia has been shown to be an independent risk factor for cardiovascular disease (CVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 238 publications
(324 reference statements)
1
35
0
1
Order By: Relevance
“…Для бляшек дистрофически-некротического вида было отмечено повышение экспрессии генов ABCA1, LIPA, LPL, SCARB1 и STAP1 [20][21][22][23].…”
Section: Discussionunclassified
“…Для бляшек дистрофически-некротического вида было отмечено повышение экспрессии генов ABCA1, LIPA, LPL, SCARB1 и STAP1 [20][21][22][23].…”
Section: Discussionunclassified
“…LPL maintains TG homeostasis in blood and is the rate-limiting enzyme for the hydrolysis of TGs that are encapsulated in the core of TGRL particles ( Wang and Eckel, 2009 ; Tada et al, 2018 ; Kumari et al, 2021 ). It has been reported that gain-of-function and loss-of-function gene mutations of LPL lead to the imbalance of plasma TG levels, thereby influencing CVD events ( Rip et al, 2006 ; Wang and Eckel, 2009 ; Burnett et al, 2019 ).…”
Section: Emerging Targets For Lowering Triglyceridementioning
confidence: 99%
“…ANGPTL is a family of secreted glycoproteins consisting of eight members (ANGPTL1-8). These proteins, especially ANGPTL3, ANGPTL4, and ANGPTL8 are found to regulate the activity of LPL ( Li et al, 2020 ; Kumari et al, 2021 ). In the following, we mainly describe several intensively studied ANGPTL members that have potential applications for treatment of HTG.…”
Section: Emerging Targets For Lowering Triglyceridementioning
confidence: 99%
“…Unlike the contradictory data from the LPL activator, abrogating the inhibitory effects of ApoC3 and ANGPTLs on LPL activity consistently reduces circulating TG levels, thus yielding promising outcomes of dyslipidemia in different experimental animal models (4). Recently, ANGPTL3 and ApoC3 have been reported to be potential therapeutic targets for the treatment of HTG in clinical trials.…”
Section: Introductionmentioning
confidence: 99%